Drug-induced movement disorder: A disproportionality analysis using the FDA adverse event reporting system (FAERS) from 2004 to 2024 - Jingjing Zou; Chenju Zhan; Yan Feng; Qixi Liu; Guohao Peng; Zhongjie Cai; Lingling Luo; Jun Zou (PLoS ONE, 2025)
Background Although many drugs have been associated with drug-induced movement disorders (DIMDs), the associated risks are unclear. This study aimed to identify high-risk drugs for DIMDs through disproportionality analysis of the Food and Drug Administration Adverse Event Reporting System (FAERS) database and to explore risk factors for DIMDs through sensitivity analysis. Methods Four disproportionality analysis methods were used to assess the risk signals of drugs that may induce DIMDs from the first quarter of 2004 to the fourth quarter of 2024. One-way analyses, LASSO analyses, and logistic regression analyses were performed to explore the risk factors associated with DIMDs. Results There are 138,081 reports related to DIMDs. This study identified 148 suspected drugs. Age under 33 years, male gender, and 62 medications, including METOCLOPRAMIDE, ARIPIPRAZOLE, CARBIDOPA, LEVODOPA, RISPERIDONE, and QUETIAPINE, are all independent risk factors for drug-induced movement disorders. The area under the ROC curve (AUC) reflecting model predictive accuracy was 0.724. Conclusion Our disproportionality analysis and sensitivity analysis of the FAERS database identified drugs potentially associated with DIMDs. These findings can provide valuable information for clinicians to be more cautious when prescribing these drugs and to monitor patients for the development of movement disorders closely. Additionally, the results can help regulatory agencies make informed decisions regarding the safety of drugs.